2020
DOI: 10.1371/journal.pone.0229268
|View full text |Cite
|
Sign up to set email alerts
|

Associations between body dissatisfaction and self-reported anxiety and depression in otherwise healthy men: A systematic review and meta-analysis

Abstract: This study provides the first pooled estimates of the correlation between body dissatisfaction and anxiety and depression in men. Findings need to be interpreted with respect to the samples and outcomes of the included studies. It is recommended that future research should increase the diversity of men in studies. Studies should measure a wider range of body dissatisfaction types found in men. Conclusion The findings demonstrate that an association between male body dissatisfaction and anxiety and depression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
73
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 57 publications
(79 reference statements)
10
73
0
3
Order By: Relevance
“…When a variable is correlated across several variables, its explanatory power in DDA is reduced ( Sherry, 2006 ; Barton et al, 2016 ). This result is consistent with previous work that found social phobia to be associated with components of emotional processing, disordered eating, and body dissatisfaction in men and women ( Keel and Forney, 2013 ; Kerr-Gaffney et al, 2018 ; Barnes et al, 2020 ). Previous researchers found elevated symptoms of social phobia to be so common in undergraduates that responses on social phobia inventories do not distinguish respondents with and without diagnosis ( Stewart and Mandrusiak, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
“…When a variable is correlated across several variables, its explanatory power in DDA is reduced ( Sherry, 2006 ; Barton et al, 2016 ). This result is consistent with previous work that found social phobia to be associated with components of emotional processing, disordered eating, and body dissatisfaction in men and women ( Keel and Forney, 2013 ; Kerr-Gaffney et al, 2018 ; Barnes et al, 2020 ). Previous researchers found elevated symptoms of social phobia to be so common in undergraduates that responses on social phobia inventories do not distinguish respondents with and without diagnosis ( Stewart and Mandrusiak, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
“…Certainly, some pre-pandemic research – mostly with samples of undergraduate women – has shown that perceived stress (i.e., a person's appraisal of stress caused by environmental conditions) and stressful life events were associated with greater body dissatisfaction (e.g., Haddad et al, 2019 ; Johnson & Wardle, 2005 ; Murray et al, 2011 ). Likewise, trait anxiety (i.e., a differential trait reflective of a tendency to worry) has been found to be significantly associated with body dissatisfaction, independently of perceived stress, in women (e.g., Davey & Chapman, 2009 ) and men ( Barnes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The low BI before surgery can be attributed to patients' poor preoperative mood and psychological status as well as fear and anxiety over surgery and death [14]. A recent review study also confirmed the associations between BI dissatisfaction and anxiety and depression [40]. Some studies have also reported that most of the patients hospitalized for CABG experience various emotions ranging from a slight fear to anxiety, depression, and fear of death, and these problems are more annoying than their chest pain [41], which consequently can affect BI [42].…”
Section: Discussionmentioning
confidence: 84%